Potential Feedstock of Rubber Seed Oil for Biodiesel Production - Hamzah, N.; Mohd Isa, S.; Ahmad Tajuddin, N. (International Journal of Engineering and Technology, 2019)
Biodiesel can help to reduce the world‘s dependence on fossil fuels and which also has significant environmental benefits. Biodiesel is a mixture of fatty acid methyl esters (FAME) obtained via transesterification of vegetable oils or animal fats with an alcohol. The rubber seed oil (RSO) is chosen as a potential non-edible vegetable oil for the production of biodiesel. The oil was extracted from the seed by using pressurized liquid extraction (ASE). The percentage rubber seed oil extracted from 2.6 kilograms rubber seed was obtained 35%. The acid value of RSO has reduced from 52.3 mg KOH/g to 0.8 mg KOH/g while FFA% value has reduced from 35% to 1.18% after acid esterification was applied to RSO. The oil was proceed with base transesterification where the triglycerides from the oil were converted into FAME. The optimization of transesterification process was performed in order to determine the optimum conditions that give the highest FAME yield. Result shows that optimum conditions of the transesterification of rubber seed oil were 1:6 of oil to methanol mass ratio ,30 wt% KOH catalyst, 60 oC reaction temperature and 60 minutes reaction time, that offering the highest biodiesel yield of 96%.